1982
DOI: 10.1080/00039896.1982.10667557
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Levels of Cadmium and Lead on Cognitive Functioning in Children

Abstract: Hair cadmium and lead content were related to intelligence tests, motor impairment assessments, and school achievement scores from 149 children aged 5 to 16 yr enrolled in rural Maryland public school systems. Hair cadmium and lead were significantly correlated with both intelligence scores and school achievement scores, but not motor impairment scores. Significant relations with I.Q. were obtained after regressing out demographic factors and were observed, even in children within a normal I.Q. range. Evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
3

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(64 citation statements)
references
References 25 publications
(2 reference statements)
0
61
0
3
Order By: Relevance
“…In case-control studies in which the hair concentration of cadmium of a clinically-defined group was compared to that of a reference group, higher concentrations were reported in mentally retarded children (68,69) and in children with learning difficulties or dyslexia (70,71), but not in children with autism (72,73) or in children with any of several neuropsychiatric diagnoses (motor, perceptual, speech, or attention disorders) (74). In cohort studies, Thatcher et al (75,76) reported that the concentration of cadmium in hair was significantly inversely related to adjusted IQ scores, particularly verbal IQ, and to visual evoked potentials; (77) and Marlowe and colleagues (78,79) reported associations between increased hair cadmium and children's performance on visual-motor tasks. Marlowe et al (80) also reported that lead and cadmium acted synergistically in impair children's classroom behavior.…”
Section: Neurotoxicity Of Cadmiummentioning
confidence: 99%
“…In case-control studies in which the hair concentration of cadmium of a clinically-defined group was compared to that of a reference group, higher concentrations were reported in mentally retarded children (68,69) and in children with learning difficulties or dyslexia (70,71), but not in children with autism (72,73) or in children with any of several neuropsychiatric diagnoses (motor, perceptual, speech, or attention disorders) (74). In cohort studies, Thatcher et al (75,76) reported that the concentration of cadmium in hair was significantly inversely related to adjusted IQ scores, particularly verbal IQ, and to visual evoked potentials; (77) and Marlowe and colleagues (78,79) reported associations between increased hair cadmium and children's performance on visual-motor tasks. Marlowe et al (80) also reported that lead and cadmium acted synergistically in impair children's classroom behavior.…”
Section: Neurotoxicity Of Cadmiummentioning
confidence: 99%
“…A detection limit in the sub ppm range (0.16 ppm) and high accuracy were reported for GFAAS analysis of hair samples (Wilhelm et al 1989). ICP/AES has also been used to analyze hair for lead, but lack of data prevents a comparison with the AAS method (Thatcher et al 1982).…”
Section: Methodsmentioning
confidence: 99%
“…In the 1970s and 1980s, both animal experiments and epidemiologic studies reported the first proofs of cadmium neurotoxicity. Prenatal Cd exposure had significantly detrimental effects on verbal IQ as well as on cognitive and visual-motor performance in children (Thatcher et al 1982;Marlowe et al 1985;Moon et al 1985;Bonithon-Kopp et al 1986), though it was not clear whether the observed outcomes were due to a coexposure to multiple pollutants, which included lead. It is important to say that these results were based on the hair Cd analysis in children, which may be subject to external contamination.…”
Section: Neurotoxic Effectsmentioning
confidence: 99%